Synthesis of Deep Eutectic Solvent (DES) Based on Glycerol and Propylene Glycol as a Medium for Anthocyanin Extraction from Senduduk Flowers (Melastoma sp.) - Sari, Indah Puspita; Amalia , Wulan; Saputra, Muhammad Yogi (Universitas Islam Indonesia, 2026)
Environmental concerns related to the extensive use of conventional organic solvents have driven the development of greener extraction technologies, including the application of deep eutectic solvents (DES) as environmentally friendly alternatives. This study aimed to evaluate the effectiveness of choline chloride–based DES combined with glycerol and propylene glycol as green solvents for anthocyanin extraction from Senduduk flowers (Melastoma sp.) using the ultrasound-assisted extraction (UAE) method. DES were synthesized at a 1:2 molar ratio and characterized based on density, viscosity, pH, moisture content, and functional group analysis using FTIR spectroscopy. The results confirmed the successful formation of DES with suitable physicochemical properties for extraction applications. Both DES systems were able to extract various bioactive compounds, including flavonoids, alkaloids, terpenoids, saponins, and tannins. The highest total anthocyanin content was obtained using choline chloride/glycerol DES (93.29 mg/L), followed by choline chloride/propylene glycol DES (89.06 mg/L). Total flavonoid contents were 86.97 mg QE/g and 85.78 mg QE/g, respectively. Antioxidant activity analysis indicated strong radical scavenging capacity with IC₅₀ values of 70.82 ppm and 72.61 ppm. These findings demonstrate that glycerol- and propylene glycol-based DES are effective green solvents for anthocyanin extraction and show potential for sustainable applications in food, pharmaceutical, and cosmetic industries.